(untitled) (Journal of Fiber Bioengineering and Informatics, 2013)
“Smart textiles”, also known as electronic or e-textiles contain embedded sensors capable of monitoring vital signals such as ECG, EMG, respiratory behaviour and are usually fabricated using rigid semiconductors. In this study, we developed a flexible Physiological Sensing Belt (PSB) by embedding silicone rubber/carbon black/conductive carbon layer coated Polyvinylidene Fluoride (PVDF) film between the elastic textile bands for monitoring respiration and the movement of thigh muscles. With an average peak-to-peak interval of 3 sec, the respiration rate could be evaluated to be 20 min^-1. We also developed a novel hybrid sensor using PVDF and Thermoplastic Polyurethane (TPU) electrospun nanofiber webs stacked on each other and capable of measuring both static and dynamic pressure simultaneously within all frequency ranges. Based on the samples used, we were able to measure the walking speed of the subject at 4, 336 steps/h and 0.693 m/step at the speed of 3 km/h and with 6, 656 steps/h and 0.751 m/step at the speed of 5 km/h. Overall, when compared to the existing commercially available pressure sensors, the PVDF and TPU nanofiber web based hybrid sensor developed in our study has advantages of high sensitivity, nanoscale thickness, lower hysteresis curve in pressure-capacitance, and can be easily converged with any fabric or textiles.